Trans-activity of plasma membrane-associated ganglioside sialyltransferase in mammalian cells - Vilcaes, Aldo Alejandro (2011)
Gangliosides are acidic glycosphingolipids that contain sialicacid residues and are expressed in nearly all vertebrate cells.They are synthesized at the Golgi complex by a combination ofglycosyltransferase activities followed by vesicular delivery tothe plasma membrane, where they participate in a variety ofphysiological as well as pathological processes. Recently, a numberof enzymes of ganglioside anabolism and catabolism havebeen shown to be associated with the plasma membrane. In particular,it was observed that CMP-NeuAc:GM3 sialyltransferase(Sial-T2) is able to sialylate GM3 at the plasma membrane (ciscatalyticactivity). In this work, we demonstrated that plasmamembrane-integrated ecto-Sial-T2 also displays a trans-catalyticactivity at the cell surface of epithelial and melanoma cells.By using a highly sensitive enzyme-linked immunosorbent assaycombined with confocal fluorescence microscopy, we observedthat ecto-Sial-T2 was able to sialylate hydrophobically or covalentlyimmobilized GM3 onto a solid surface. More interestingly,we observed that ecto-Sial-T2 was able to sialylate GM3exposed on the membrane of neighboring cells by using both theexogenous and endogenous donor substrate (CMP-N-acetylneuraminicacid) available at the extracellular milieu. In addition,the trans-activity of ecto-Sial-T2 was considerably reducedwhen the expression of the acceptor substrate was inhibited byusing a specific inhibitor of biosynthesis of glycolipids, indicatingthe lipidic nature of the acceptor. Our findings provide thefirst direct evidence that an ecto-sialyltransferase is able totrans-sialylate substrates exposed in the plasma membranefrom mammalian cells, which represents a novel insight into themolecular events that regulate the local glycosphingolipidcomposition.